Goreisan inhibits vascular endothelial cell migration and angiogenesis. Issue 1 (3rd February 2021) - Murakami, Kazuhito; Horie, Ichiro; Isohama, Yoichiro
Abstract: Aim: Goreisan (GRS) is a Japanese Kampo medicine, which has been clinically used to treat edema and headache. Recently, a clinical study indicated that GRS significantly suppresses the recurrence of chronic subdural hematoma (CSDH). In CSDH, leakage from immature blood vessels on the neomembrane is involved in the recurrence or exacerbation. Although several clinical reports have shown the effectiveness of GRS, the pharmacological properties and underlining mechanism of GRS are not clear. In this study, we examined the effect of GRS on the migration and proliferation of vascular endothelial cells via in vitro and in vivo experiments. Method: Human umbilical vascular endothelial cells (HUVECs) were treated with vascular endothelial growth factor (VEGF) for 24 h, and migration ability, extracellular signal‐regulated kinase (ERK) phosphorylation level, and aquaporin‐1 (AQP1) expression level were measured. Matrigel containing VEGF was injected subcutaneously into the abdomen of C57BL mice (Matrigel plug assay). After oral administration of GRS for seven days, the effect on angiogenesis was examined by immunostaining. Results: GRS inhibited VEGF‐induced migration in a dose‐dependent manner. GRS also inhibited VEGF‐induced phosphorylation of ERK, which is a major signaling molecule for the migration. In addition, GRS markedly decreased protein and mRNA expression of AQP1, which is another important regulator of endothelial cell migration. Finally, GRS inhibited angiogenesis, as revealed by in vivo Matrigel plug assay. Conclusion: The findings indicated that GRS can suppress angiogenesis through inhibiting the migration of endothelial cells by downregulating ERK activation and aquaporin‐1 expression, leading to the preventive effect of GRS against CSDH recurrence.